Ukrainian Folk Ornaments in Modern Knitting - Liudmyla Melnyk; Olena Kyzymchuk; Liudmyla Zubkova (Tekstilec, 2021)
National arts and crafts are not only the skills of an individual nation but an ethnic phenomenon that has unique features and serves as a source of information on national history and culture. Decorative and applied art in Ukraine combines the traditions and techniques of manufacturing and decoration, which have been developed and passed down from generation to generation. It has a clear national identity and numerous regional differences in ornamental motifs, compositions and favourite colours. Therefore, the Ukrainian folk art has a significant potential and is a source of ideas in creating modern clothing as well as interior items. Embroidery as a way of creating ornamental motifs on a textile material using various techniques is a common process for decorating clothes and interiors for the Ukrainians. Today, ornamental compositions of embroidered folk textiles could be transmitted into modern clothes using various technologies. However, the use of a knitting machine allows creating a pattern during the item production. The ornament transformation into a pattern for knitting can be carried out with graphic software by creating a grid with a cell size similar to the loop size of a knitted structure for corresponding interlooping. A number of clothing and interior items with ethnic motifs was created using the capabilities of flat knitting machines within the masters programme “Knitting Technology and Design” at the Textile Technology and Design Department of the Kyiv National University of Technologies and Design.